Educational Communication Model of the Prophet Muhammad in Tarbawi ‎Hadith: A Study of Dialogic and Humanistic Patterns - Muflikhatun Muflikhatun; A Ghani; Muhammad Akmansyah; Amirudin Amirudin (at-Tarbiyah al-Mustamirrah: Jurnal Pendidikan Islam, 2026)
The educational communication of the Prophet Muhammad in tarbawi hadith constitutes an important source for understanding a pedagogical approach that integrates dialogic and humanistic patterns. This study aims to explore the educational communication model of the Prophet Muhammad based on authentic hadiths and to analyze its relevance to modern education. This research employed a qualitative approach with a library research design. The main data sources consisted of authentic hadiths that describe the Prophet’s communication with his companions and wider society. The data were analyzed using thematic analysis to identify dialogic and humanistic patterns. The findings show that the Prophet’s dialogic communication pattern is highly relevant to student-centered learning in modern education, particularly in encouraging active participation, reflective reasoning, and critical thinking. In addition, the humanistic pattern, grounded in empathy and respect for individual dignity, contributes significantly to the formation of students’ moral character. The dialogic and humanistic dimensions of the Prophet’s communication provide a theoretical contribution to the development of Islamic educational communication theory that can be applied in contemporary education. These patterns are also relevant for addressing twenty-first-century educational challenges, including moral crises and the need to strengthen students’ social skills. The Prophet’s educational communication model offers an inclusive and character-oriented approach that can help improve communication practices and moral formation among young people.